HYGIENE SANITATION AND FOOD SAFETY IN EMPLOYEE RESTAURANTS - Herniwanti; Jayanti, Dwi (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Restaurants is a food processing place that produces and sells various types of food and beverages for the wider community. With the development of restaurants, it is necessary to make food and beverage health efforts with the aim that people's ability to manage can be increased so that people avoid health problems or food poisoning. One of the efforts that can be done is to check the feasibility of the restaurant's hygiene and sanitation. The purpose of this study was for this examination to determine hygiene and sanitation in employee restaurants from 4 factors, employee, equipment, food, and place. The research method used is descriptive qualitative by evaluating employee restaurants in the mess area of industrial forest plantation companies by filling out a restaurant sanitation hygiene inspection form issued by the Directorate of Environmental Health of the Republic of Indonesia in 2017, informant from owner and canteen employee. The results show that the restaurant building is semi-permanent. Workers do not have uniforms and do not carry out routine health checks. Food storage cabinet equipment is not available properly for foodstuffs that require closed storage and room temperature. Clean water sources and hand washing facilities and toilets are well available. The food preparation provides a varied menu but the calories are not calculated for the nutritional value. It is recommended for companies and restaurant managers to manage menu calculations that are sufficient in calories and nutrition for employees, provide safer food storage places, and employees are also advised to use uniforms and health checks to keep food from contamination so that consumers can receive healthy food that is also safe for consumption.